Virtual Learning Method During The Covid Pandemic Era - Metekohy, Benyamin; Sahertia, Novita Loma; Ming, David (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2024)
The COVID-19 epidemic has enabled students to study and teachers to teach remotely. Teachers must be able to modify course materials so that students are taught the proper methods. Research on education during the epidemic reveals two broad patterns. 1. According to current research, instructors are a cause of worry for pupils during the epidemic. 2. In place of instructors, both studies stress the importance of parents being involved in their children's education. This report aims to address the issue of instructors and students not communicating effectively throughout the epidemic. Primary and secondary data were used, and research informants included instructors, students, parents, and security personnel. Participants in the study were chosen using the direct experience criterion.